EDUCATION CHARACTER IN VIEW OF AL-GHAZALI AND ITS RELEVANCE WITH THE EDUCATION CHARACTER IN INDONESIA - Atik Wartini (Ta'dib: Jurnal Pendidikan Islam, 2015)
This research is based on research library, the background of this research concerns with the deterioration of morals or character education in children and adolescents. Foreign cultures that are not properly filtered is the result of deterioration of education and children‘s akhlak. Imam al-Ghazali, one of the leaders of Islamic thinker that has miraculous works, one of the famous works is the book of al-walad ayyuha, described the mechanism in the moral education of children and adolescents. Education behavior is defined by al-Ghazali in this book are relevant with the character education for children and adolescents.